Combining the Use of Reflective Groundcovers and Aminoethoxyvinylglycine to Assess Effects on Skin Color, Preharvest Drop, and Quality of ‘Honeycrisp’ Apples in the Mid-Atlantic US - Md Shipon Miah; Macarena Farcuh (Horticulturae, 2024)
Apples are one of the most valuable fruits worldwide. ‘Honeycrisp’ is the top sales-producing cultivar in the US. Lack of red skin coloration and increased preharvest fruit drop significantly reduce the market value for cultivars such as ‘Honeycrisp’. The use of reflective groundcovers has been shown to enhance apple skin coloration. While the use of plant growth regulator AVG reduces fruit drop, it negatively affects skin coloration. Studies on the impacts of these practices in mid-Atlantic US-grown apples are limited. In this work, for two years, we compared differences in the light environment, fruit drop, internal ethylene concentration (IEC), physicochemical parameters, and skin coloration of ‘Honeycrisp’ apples in the lower third of the canopy. Apples were submitted to four treatment combinations of reflective groundcover (Extenday) and AVG (130 mg L−1). Assessments occurred throughout three ripening stages. Our results demonstrated that Extenday significantly promoted skin coloration (>75% blush) via the increased reflectance of photosynthetic photon flux density and UV radiation, and increased IEC, while also advancing fruit maturity, i.e., overripening. Conversely, AVG significantly minimized fruit drop and decreased EIC, delaying fruit maturity but drastically reducing red coloration (30–48% blush). The combined use of Extenday and AVG had a synergistic effect by decreasing fruit drop while enhancing fruit with >50% blush, without promoting overripening. Combining Extenday and AVG can boost the market value for ‘Honeycrisp’ apples in the mid-Atlantic US.